Bajbuza : czasy Zygmunta III - Kraszewski, Jozef Ignacy, 1812-1887. (Warszawa : Ludowa Spoldzielnia Wydawnicza, 1986)
An historical novel taking place in the reign of Sigismund III in the 17th century.
P86-3282
BO 95059 10sep86 JWH
Keywords: Poland -- History -- Sigismund III, 1587-1632 -- Fiction